Requirement for p62 acetylation in the aggregation of ubiquitylated proteins under nutrient stress - Zhiyuan You; Wen-Xue Jiang; Ling-Yun Qin; Zhou Gong; Wei Wan; Jin Li; Yusha Wang; Hongtao Zhang; Chao Peng; Tianhua Zhou; Chun Tang; Wei Liu (Nature Communications, 2019)
The autophagy receptor p62 mediates the assembly and removal of ubiquitylated protein aggregates by forming p62 bodies. Here, the authors identify an acetylation-dependent mechanism that regulates formation and autophagic clearance of p62 bodies under nutrient-deficient conditions.